Communal irrigation systems in South-Eastern Africa: findings on productivity and profitability. Issue 5 (3rd September 2017) - Pittock, Jamie; Bjornlund, Henning; Stirzaker, Richard; van Rooyen, Andre
Abstract: Significant expansion of irrigated agriculture is planned in Africa, though existing smallholder schemes perform poorly. Research at six schemes in Mozambique, Tanzania and Zimbabwe shows that a range of problems are exacerbated by poor management, with limited market linkages leading to underutilization and a lack of profit. Improving sustainability of these complex systems will require: multiple interventions at different scales; investing in people and institutions as much as hardware; clarity in governments' objectives for their smallholder irrigation schemes; appropriate business models to enable farmers; and better market linkages.